STRATEGY FOR COACHING AND DEVELOPMENT OF SPORTS ACHIEVEMENT BRANCHES IN SUPPORTING THE SUCCESSFUL IMPLEMENTATION OF THE NATIONAL SPORTS GRAND DESIGN (DBON) IN BENGKULU PROVINCE - Atisar; Lizar Alfansi; Slamet Widodo; Muhartini Salim (International Journal Management and Economic, 2024)
The purpose of this study is to identify internal and external factors and formulate strategies for coaching and developing superior sports achievements in Bengkulu Province. This research is a design of survey research, which is research that takes samples from a population that uses questionnaires as a data collection tool. The design of data used is primary data obtained through questionnaires. The research samples are some of the stakeholders of coaching and developing leading sports in Bengkulu Province such as the Indonesian National Sports Committee (KONI) Bengkulu, Youth and Sports Office, Sports Coaches, Sports Athletes, Sports Observers, Sports Industry and Sports Society in Bengkulu totaling 80 people. The sampling method used purposive sampling. The data analysis methods used are descriptive analysis, SWOT analysis and qualitative analysis. Based on the results of data analysis, it is known that: the Evaluation of internal factors (IFAS) and external factors (EFAS) to obtain strategies for coaching and developing regional leading sports in Bengkulu Province in supporting the successful implementation of DBON is an S-O strategy (aggressive strategy), namely: (a) Fostering public interest in sports through sports promotion efforts (S2;O2); (b) Coaching athletes in community sports clubs through the provision of coaching budgets (S4;O2); (c) Conduct regular coordination and coaching between the management and athletes of each sport and involve the sports community (S2;O4) and (d) Provide planned awards to sportsmen so that sports become a profession (S4;O4).